2004
DOI: 10.1038/sj.bmt.1704473
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 96 patients with advanced ovarian carcinoma treated with high-dose chemotherapy and autologous stem cell transplantation

Abstract: Summary:The purpose of this study was to identify characteristics significant to survival and progression-free survival in patients with advanced ovarian cancer receiving high-dose chemotherapy. In all, 96 patients received autologous stem cell transplantation. Regimens included paclitaxel with carboplatin (PC), topotecan, melphalan, cyclophosphamide (TMC) and cyclophosphamide, BCNU, thiotepa (CBT). At the time of transplantation, 43% of patients were in clinical CR, 34% were in clinical PR, 18% had progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…CP is one of the most effective chemotherapeutic agents used in the treatment of cancers of breast (Levine et al, 2005;Hirano et al, 2008), lung (Sundstrom et al, 2005;Zhang et al, 2006), prostate (Nicolini et al, 2004), ovary (Donato et al, 2004), leukemia (Rao et al, 2005), lymphomas and non-Hodgkin's lymphoma. Significantly different from the CP-treated group using one-way ANOVA followed by the Tukey-Kramer multiple comparisons test (p50.05).…”
Section: Discussionmentioning
confidence: 99%
“…CP is one of the most effective chemotherapeutic agents used in the treatment of cancers of breast (Levine et al, 2005;Hirano et al, 2008), lung (Sundstrom et al, 2005;Zhang et al, 2006), prostate (Nicolini et al, 2004), ovary (Donato et al, 2004), leukemia (Rao et al, 2005), lymphomas and non-Hodgkin's lymphoma. Significantly different from the CP-treated group using one-way ANOVA followed by the Tukey-Kramer multiple comparisons test (p50.05).…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate for International Federation of Gynecology and Obstetrics (FIGO) Stage III disease is approximately 20-25% (1)(2)(3)(4)(5). Various sorts of consolidation therapy have been studied in a series of clinical trials, but none has shown to improve survival in ovarian cancer (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Stiff et al 19 have reported the largest single centre experience of high-dose consolidation chemotherapy for relapsed ovarian cancer. This study shows that the best 20 and by Donato et al: 21 the survival of patients treated with highdose chemotherapy in CR was significantly better than that observed in other groups of patients. Another recently published randomised trial showed a trend for a better outcome for patients in CR treated with i.p.…”
Section: Discussionmentioning
confidence: 67%